Review of the grass feeding leafhopper genus Hecalus Stål (Hemiptera: Cicadellidae: Deltocephalinae) with description of four new species from Pakistan - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
The leafhopper genus Hecalus Stål is reviewed first time from Pakistan. Four new species (H. erectus, H. muzaffarabadensis, H. snipus, and H. veracious, spp. nov.) with a new record of H. ghaurii Rao & Ramakrishnan, 1990 from Pakistan are described. A key to distinguish all Pakistani species in this genus is provided. Descriptions of male genitalia are provided for the known species.